Oxidative Stress, Inflammation, and Autophagy: Potential Targets of Mesenchymal Stem Cells-Based Therapies in Ischemic Stroke - He, Jialin; Liu, Jianyang; Huang, Yan; Tang, Xiangqi; Xiao, Han; Hu, Zhiping (Frontiers in Neuroscience, 2021)
Ischemic stroke is a leading cause of death worldwide, currently available treatment approaches for ischemic stroke are to restore blood flow, which reduce disability but are time-limited. The interruption of blood flow in ischemic stroke contributes to intricate pathophysiological processes. Oxidative stress and inflammatory activity are two early events in the cascade of cerebral ischemic injury. These two factors are reciprocal causation and directly trigger the development of autophagy. Appropriate autophagy activity contributes to brain recovery by reducing oxidative stress and inflammatory activity, while autophagy dysfunction aggravates cerebral injury. Abundant evidence demonstrates the beneficial impact of mesenchymal stem cells (MSCs) and secretome on cerebral ischemic injury. MSCs reduce oxidative stress through suppressing ROS and RNS generation and transferring healthy mitochondria to damaged cells. Meanwhile, MSCs exert anti-inflammation properties by the production of cytokines and extracellular vesicles, inhibiting pro-inflammatory cytokines and inflammatory cells activation, suppressing pyroptosis, and alleviating blood-brain barrier leakage. Additionally, MSCs regulation of autophagy imbalances give rise to neuroprotection against cerebral ischemic injury. Altogether, MSCs have provided a promising candidate for the treatment of ischemic stroke due to their pleiotropic effect.